2017
DOI: 10.1377/hlthaff.2017.0211
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospital Readmissions Through Preferred Networks Of Skilled Nursing Facilities

Abstract: Establishing preferred provider networks of skilled nursing facilities (SNFs) is one approach hospital administrators are using to reduce excess thirty-day readmissions and avoid Medicare penalties or to reduce beneficiaries’ costs as part of value-based payment models. However, hospitals are also required to provide patients at discharge with a list of Medicare-eligible providers and cannot explicitly restrict patient choice. This requirement complicates the development of a SNF network. Furthermore, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 11 publications
1
73
2
Order By: Relevance
“…As such, implementing HIE to support transitions of care is rarely an isolated strategy. 15,19,20 However, even with other concurrent changes our study hospital may have made around the time of HIE rollout, our results suggest no overall beneficial treatment effect from these efforts. This null average treatment effect could, however, be muting beneficial impact for certain patient subpopulations in ways we are not well-positioned to detect.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…As such, implementing HIE to support transitions of care is rarely an isolated strategy. 15,19,20 However, even with other concurrent changes our study hospital may have made around the time of HIE rollout, our results suggest no overall beneficial treatment effect from these efforts. This null average treatment effect could, however, be muting beneficial impact for certain patient subpopulations in ways we are not well-positioned to detect.…”
Section: Discussioncontrasting
confidence: 56%
“…Hospitals are facing increasing financial accountability for patients’ total cost of care and are tightening referral networks with select postacute providers, investing more selectively with these organizational partners in improved infrastructure and integrated handoff processes. As such, implementing HIE to support transitions of care is rarely an isolated strategy . However, even with other concurrent changes our study hospital may have made around the time of HIE rollout, our results suggest no overall beneficial treatment effect from these efforts.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Prior research found that, on average, hospitals discharged patients to more than 37 SNFs and 23 home health agencies . One response to the wide dispersion of post‐acute care discharges has been the establishment of “preferred networks” of SNFs or other post‐acute care providers by accountable care organizations and bundled payment awardees . In such networks, SNFs may agree to jointly implement care protocols, share information, and reduce length of stay in exchange for a higher volume of patients from the hospital or accountable care organization .…”
mentioning
confidence: 99%